2015
DOI: 10.3923/jfas.2016.28.42
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Synbiotic Microcapsule Influence the Immune Responses, Growth Performance and Microbial Populations to White Spot Syndrome Virus in Pacific White Shrimp (Litopenaeus vannamei)

Abstract: White Spot Syndrome Virus (WSSV) is one of the most devastating shrimp pathogen which causes up to 70-90% mortality in commercial shrimp farming. This study was aimed to evaluate the effectiveness of synbiotic microcapsule (Bacillus NP5 Rf R and mannan oligosaccharide combination) feed supplementation on the immune responses and growth performance of WSSV infected Pacific white shrimp. Shrimps (4.411±0.395 g) were cultured and fed by pellet containing synbiotic microcapsule at different dosages for 30 days, i.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…13 In our study, low amounts of liquid animal vermicompost as a supplement in shrimp food yield eda good response in shrimp growth and survival. 13,14 Febrianti et al 15 reported that dietary symbiotic microcapsules could improve the absorption of nutrients and growth performance, this statement can be applied to the vermicompost that can be absorbed by bacterial metabolism in the gut. 5,16 Yao et al 17 mention that crude protein can be improved significantly with these diets of additives supplementation; some studies have reported that organic acids, such as liquid vermicompost, can improve growth, feed utilization, gut health, and disease resistance in aquatic animals, and will benefit shrimp farming in water reservoirs and closed recirculating water culture systems.…”
Section: Discussionmentioning
confidence: 99%
“…13 In our study, low amounts of liquid animal vermicompost as a supplement in shrimp food yield eda good response in shrimp growth and survival. 13,14 Febrianti et al 15 reported that dietary symbiotic microcapsules could improve the absorption of nutrients and growth performance, this statement can be applied to the vermicompost that can be absorbed by bacterial metabolism in the gut. 5,16 Yao et al 17 mention that crude protein can be improved significantly with these diets of additives supplementation; some studies have reported that organic acids, such as liquid vermicompost, can improve growth, feed utilization, gut health, and disease resistance in aquatic animals, and will benefit shrimp farming in water reservoirs and closed recirculating water culture systems.…”
Section: Discussionmentioning
confidence: 99%
“…Several things are still obstacles to achieving the national shrimp production target, both for export needs and domestic shrimp consumption. Various types of infectious diseases due to viral and bacterial infections are still the main obstacles to white shrimp cultivation in Indonesia (Munaeni et al, 2014;Nurhayati et al, 2015;Febrianti et al, 2016;Yunarty et al, 2016;Utomo et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The combination of prebiotics with probiotics is called synbiotics, which have been shown to have a synergistic effect on the host [6]. Several studies reported that the administration of synbiotics could improve growth performance, survival, and immune response of Pacific white shrimp [7,8,9].…”
Section: Introductionmentioning
confidence: 99%